Bone apposition and surface treatment in dental implants: histomorphometric pilot evaluation in rabbits - Lourenço, Marcos Nunes; Sartori, Elisa Mattias; Padovan, Luis Eduardo Marques; Thomé, Geninho; Faeda, Rafael Silveira [UNESP]; Marcantonio Júnior, Elcio [UNESP]; Claudino, Marcela (My University, 2013)
The surface of dental implants is an important factor for osseointegration process and different methods of surface treatment have been described. Objective: To investigate the bone apposition in implant surface treated with sandblasting and acid-etching. Material and methods: Ten rabbits were selected and received one implant treated with method I in the left tibia and one implant treated with method II in the right tibia. Then, twenty implants were divided in two groups, according to methods of sandblasting and acid-etching (method I and method II). After 7, 14, 30, 45 and 60 days, tibias were retrieved and submitted to histotechnical procedures. The percentages of bone–implant contact (BIC) and bone area between threads (BABT) were determined throughout histomorphometric analysis and bone apposition was detected in implants of both groups. Results: In BABT measurements, an increase was observed after 45 and 60 days in the method II, compared to method I and no differences were found after 7, 14 and 30 days. In BIC measurements, an increase was detected with method II at 45 days when compared to method I. No differences between groups in BIC values were observed after 7, 14, 30 and 60 days. Conclusion: Our data demonstrated that implants treated with the method II presented increase in the contact between bone and implant after 45 days compared to method I. Moreover, with concern to bone area between threads, it was observed an increased in the method II after 45 and 60 days. However, both groups can be successfully used as a therapeutic strategy to rehabilitation of edentulous patients. Then, further experiments are needed to evaluate, in depth, the putative differential role of each surface treatment.
Keywords: Osseointegration; Dental implant; Osteogenesis; Titanium